On compensation of discrete Fourier transform error - David G. Asatryan (Изд-во НАН РА)
A problem of reduction of the percentage (relative) error, appearing at a ¯nite signal spectrum restoration by means of Discrete Fourier Transform is considered. A method based on using of a ¯nite impulse ¯lter with various impulse responses is o®ered. Depending on errors of the initial spectrum, a percentage error expression derivable after using the ¯ltering is obtained. A criterion for comparison between speci¯ed errors at a large number of discrete points is o®ered. Conditions, when the ¯lter of given response reduces the restoration error module, are obtained. Examples with uniform window and some ¯nite functions of standard type are considered. Keywords - FFT, discretization error, spectrum, spectrum restoration, ¯nite impulse ¯lter, error compensation.
Keywords: Mathematics